W.L. Caricofe, Jr. discharging loose pulp at Hercules Hopewell plant - Hercules Incorporated (1945)
General view of employee W.L. Caricofe, Jr. discharging loose pulp from a dryer at the Hercules Powder Company plant in Hopewell, Virginia. The loose pulp dryer was likely used to process cellulosic fibrous materials, such as chemical cotton (purified cellulose obtained from raw cotton linters), manufactured at the plant. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Cotton; Hercules Incorporated; Corporations; Cellulose; Machinery; Caricofe, W.L., Jr.